2011
DOI: 10.1534/genetics.111.134007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Manganese Antioxidants by Nutrient Sensing Pathways in Saccharomyces cerevisiae

Abstract: In aerobic organisms, protection from oxidative damage involves the combined action of enzymatic and nonproteinaceous cellular factors that collectively remove harmful reactive oxygen species. One class of nonproteinaceous antioxidants includes small molecule complexes of manganese (Mn) that can scavenge superoxide anion radicals and provide a backup for superoxide dismutase enzymes. Such Mn antioxidants have been identified in diverse organisms; however, nothing regarding their physiology in the context of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 57 publications
(95 reference statements)
1
28
0
Order By: Relevance
“…Seminal studies by Archibald and Fridovich (39,59) identified the manganese-antioxidant as a superoxide-scavenging activity in extracts of L. plantarum that was dialyzable and heat-and protease-resistant but susceptible to metal chelation by EDTA. Similar findings have since been reported for cell-free lysates of E. coli (41), D. radiodurans (60), Bacillus subtilis (42), and the bakers' yeast S. cerevisiae (43,61). The hexaquo Mn 2ϩ cation is a weak scavenger of superoxide, but when liganded to small molecules such as orthophosphate or carboxylates (e.g.…”
Section: Complex Mixtures Of Manganese Can Serve As Non-sod Antioxidantssupporting
confidence: 77%
See 2 more Smart Citations
“…Seminal studies by Archibald and Fridovich (39,59) identified the manganese-antioxidant as a superoxide-scavenging activity in extracts of L. plantarum that was dialyzable and heat-and protease-resistant but susceptible to metal chelation by EDTA. Similar findings have since been reported for cell-free lysates of E. coli (41), D. radiodurans (60), Bacillus subtilis (42), and the bakers' yeast S. cerevisiae (43,61). The hexaquo Mn 2ϩ cation is a weak scavenger of superoxide, but when liganded to small molecules such as orthophosphate or carboxylates (e.g.…”
Section: Complex Mixtures Of Manganese Can Serve As Non-sod Antioxidantssupporting
confidence: 77%
“…SOD, peroxidases, and catalases) are regulated during oxidative stress (71). In our recent studies with S. cerevisiae, we provided evidence to the contrary: like their enzymatic counterparts, the formation of non-proteinaceous manganeseantioxidants is tightly regulated according to cellular need (61). In particular, we found that conserved nutrient-sensing and nutrient-signaling pathways control the efficacy of intracellular manganese as a non-SOD antioxidant (61).…”
Section: Cellular Control Of Manganese-antioxidants In a Eukaryotic Mmentioning
confidence: 78%
See 1 more Smart Citation
“…Manganese (Mn) is an important antioxidant that scavenges free radicals and is secondary to biochemical functions, behaving as a backup free radical scavenger that is similar to MnSOD, especially in regard to oxidative stress (Reddi & Culotta, 2011).…”
Section: Ethnicity and Dietary Antioxidant Intakementioning
confidence: 99%
“…Although there is a lack of data on the mechanism by which Mn participates in the cellular adaptation to oxidative stress (Reddi & Culotta, 2011), research has shown that the antioxidant activity is regulated by nutrient-sensing pathways.…”
Section: Ethnicity and Dietary Antioxidant Intakementioning
confidence: 99%